Research Progress of Biomarkers for Immune Checkpoint Inhibitors on Digestive System Cancers - Wang, Jingting; Ma, Xiao; Ma, Zhongjun; Ma, Yan; Wang, Jing; Cao, Bangwei (Frontiers in Immunology, 2022)
Immunotherapy represented by immune checkpoint inhibitors has gradually entered a new era of precision medicine. In view of the limited clinical benefits of immunotherapy in patients with digestive system cancers, as well as the side-effects and high treatment costs, development of biomarkers to predict the efficacy of immune therapy is a key imperative. In this article, we review the available evidence of the value of microsatellite mismatch repair, tumor mutation burden, specific mutated genes or pathways, PD-L1 expression, immune-related adverse reactions, blood biomarkers, and patient-related biomarkers in predicting the efficacy of immunotherapy against digestive system cancers. Establishment of dynamic personalized prediction models based on multiple biomarkers is a promising area for future research.